Early Biblical Hebrew, Late Biblical Hebrew, and Linguistic Variability: A Sociolinguistic Evaluation of the Linguistic Dating of Biblical Texts. By Dong-Hyuk Kim - Stökl, Jonathan (The journal of theological studies, 2014)
This book stands in a good tradition of relatively small volumes (only 161 pages of text + 23 pages of bibliography and indexes) that address complex and important topics. Kim aims at overcoming the impasse that the debate on the linguistic dating of biblical texts has been moving towards in the last few years, after Young, Rezetko, and Ehrensvärd’s volume Linguistic Dating of Biblical Texts (2008) in which they attacked Avi Hurvitz’s model and methodology for dating biblical texts. They do not deny the variation in the text, but instead of explaining it as the result of (recognizable) change over time they argue that other factors such as style are more likely explanations for the variation in forms that have been identified.